1968
DOI: 10.1901/jaba.1968.1-167
|View full text |Cite
|
Sign up to set email alerts
|

COLLATERAL SOCIAL DEVELOPMENT ACCOMPANYING REINFORCEMENT OF OUTDOOR PLAY IN A PRESCHOOL CHILD1,2

Abstract: A 3-yr-old preschool girl with deficits in both motor and social repertoires was socially reinforced by teachers for use of outdoor play equipment, as a contribution to her motor skills and as a tactic to produce increased social contact with other children. Her use of outdoor play equipment, and various examples of her social interaction with both teachers and children were scored in the course of experimental development and analysis of her rate of equipment use. Equipment use increased greatly under the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
0

Year Published

1970
1970
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(55 citation statements)
references
References 2 publications
4
51
0
Order By: Relevance
“…Collateral improvements in social behavior have been noted (Buell, Stoddard, Harris, & Baer, 1968), suggesting that this is a possible side effect of increased gross-motor activity. Behavioral research, therefore, provides some support for educators who advocate the use of perceptual-motor training programs.…”
mentioning
confidence: 99%
“…Collateral improvements in social behavior have been noted (Buell, Stoddard, Harris, & Baer, 1968), suggesting that this is a possible side effect of increased gross-motor activity. Behavioral research, therefore, provides some support for educators who advocate the use of perceptual-motor training programs.…”
mentioning
confidence: 99%
“…In many studies, teacher approval is operationalized as verbal praise (Hall, Panyan, Rabon, and Broden, 1968;McAllister, Stachowiak, Baer, and Conderman, 1969;Ward and Baker, 1968;Wasik, Senn, Welch, and Cooper, 1969). Yet, in other studies, verbal approval is supplemented with nonverbal attending behaviors on the part of the teacher such as smiling, patting, holding, touching, moving toward the child, making eye contact, varying tone of voice, among others (Becker, Madsen, Arnold, and Thomas, 1967;Buell, Stoddard, Harris, and Baer, 1968;Cooper, Thomson, and Baer, 1970 their individual effect on student behavior is rarely evaluated. Even when observational codes include nonverbal teacher behaviors such as facial expressions and physical contact (Becker et al, 1967) or proximity of the teacher to the pupil , it remains unclear whether these behaviors contribute to behavior change in the students independently of verbal approval alone.…”
mentioning
confidence: 99%
“…Reynolds and Risley (1968) demonstrated that material as well as social reinforcers could be used to modify social behavior in the nursery. Buell, Stoddard, Harris, and Baer (1968) The present experiment attempted to increase the rate of interaction between an isolate boy and his nursery school classmates. The study was designed to minimize the time and effort required of the teacher.…”
mentioning
confidence: 99%
“…In addition, it was possible that the child's peers would react in a socially reinforcing manner to being given candy and that this would further strengthen his interaction behavior. The strategy was similar to Buell et al (1968), who strengthened one kind of behavior likely to facilitate peer reinforcement for other forms of social behavior.…”
mentioning
confidence: 99%